Retention in Medical Care Among Insured Adolescents and Young Adults With Diagnosed HIV Infection, United States, 2010-2014. (July 2022) - Tanner, Mary R.; Bush, Tim; Nesheim, Steven R.; Weidle, Paul J.; Byrd, Kathy K.
Objectives: Retention in care is a critical component of effective HIV treatment, and adolescents and young adults are at higher risk of inadequate retention than older adults. The objective of our study was to examine the patterns of retention in care among adolescents and young adults with HIV infection by analyzing Medicaid and commercial health insurance claims data. Methods: We evaluated retention in care for HIV-diagnosed adolescents and young adults aged 13-24 using the 2010-2014 MarketScan Medicaid and MarketScan Commercial Claims health insurance databases. The study period extended 36 months from the date of the first claim with a code for HIV or AIDS. We determined the unweighted proportion retained in care for the Medicaid and Commercial Claims cohorts for months 0-24 and 25-36. We assessed associations between demographic characteristics and retention in care using logistic regression. Results: A total of 378 adolescents and young adults were in the Medicaid cohort and 1028 in the Commercial Claims cohort. In the Medicaid and Commercial Claims cohorts, respectively, 186 (49%) and 591 (57%) adolescents and young adults were retained in care during months 0-24. In the Medicaid cohort, 113 (73%) people retained in care and 69 (45%) people not retained in care during months 0-24 were retained in care during months 25-36. In the Commercial Claims cohort, 313 (77%) and 94 (31%) retained and not retained people, respectively, were found to be in care during months 25-36. Conclusions: Notable proportions of HIV-diagnosed adolescents and young adults are not adequately retained in care; public health interventions tailored to this population are needed.